Mechanism of α-synuclein translocation through a VDAC nanopore revealed by energy landscape modeling of escape time distributions. Issue 1 (1st December 2016) - Hoogerheide, David P.; Gurnev, Philip A.; Rostovtseva, Tatiana K.; Bezrukov, Sergey M.
Abstract : We probe the energy landscape governing the passage of α-synuclein, a natural "diblock copolymer"-like polypeptide, through a nanoscale pore. Abstract : We probe the energy landscape governing the passage of α-synuclein, a natural "diblock copolymer"-like polypeptide, through a nanoscale pore. α-Synuclein is an intrinsically disordered neuronal protein associated with Parkinson's pathology. The motion of this electrically heterogeneous polymer in the β-barrel voltage-dependent anion channel (VDAC) of the mitochondrial outer membrane strongly depends on the properties of both the charged and uncharged regions of the α-synuclein polymer. We model this motion in two ways. First, a simple Markov model accounts for the transitions of the channel between the states of different occupancy by α-synuclein. Second, the detailed energy landscape of this motion can be accounted for using a drift-diffusion framework that incorporates the α-synuclein binding energy and the free energy cost of its confinement in the VDAC pore. The models directly predict the probability of α-synuclein translocation across the mitochondrial outer membrane, with immediate implications for the physiological role of α-synuclein in regulation of mitochondrial bioenergetics. Time-resolved measurements of the electrical properties of VDAC occupied by α-synuclein reveal distinct effects of the motion of the junction separating the differently charged regions of the polymer.